Pengaruh Wom Dan Citra Merek Terhadap Minat Beli Ulang Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada Toko Deco 100 Kuala Tanjung - Nainggolan, Benhart; Suwadi, Suwadi (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This study aims to determine the influence of wom and brand image on repurchase interest with consumer satisfaction as an intervening variable at Deco 100 Kuala Tanjung store. The research method used was a quantitative method using the help of SPSS version 25.00.which was collected from the results of distributing questionnaires to 96 Kuala Tanjung Deco 100 customers. The analytical method used in this study is using instrument tests, namely validity and reliability tests. Classical assumption tests are normality tests, multicolonearity tests, heteroscedasity tests, multiple linear regression analysis, coefficient of determination analysis (R2), hypothesis tests, namely T tests and path analysis (Path analysis). The results of SPSS in this study are Word Of Mouth variables affect consumer satisfaction, Brand Image variables affect consumer satisfaction, Word Of Mouth variables affect Repurchase Interest, Brand Image variables affect Repurchase Interest, consumer satisfaction variables affect Repurchase Interest And path analysis shows Word Of Mouth has no effect on Repurchase Interest through consumer satisfaction, and Brand Image has no effect on Repurchase Interest through consumer satisfaction.